CIVIC CULTURE DALAM NILAI-NILAI BUDAYA DAN KEARIFAN LOKAL MASYARAKAT BALI AGA DESA TRUNYAN - Mahardika, I Wayan Trisna; Darmawan, Cecep (HUMANIKA, 2016)
This research aims to see the civic culture on the culture and local wisdom of Bali Aga people in Trunyan, as well as to find how to preserve that. The method which used is qualitative with ethnography approach. The result shows that there is civic culture in the culture and local wisdom of Bali Aga people. That is found on culture of Ngayah, Paruman, Mepasah, and Barong Brutuk also in the value of local wisdom called Menyama Braya. The result also shows the preservation is run naturally along with belief in their ancestors and the bond between people and tradition.